Functional study of common bean isoliquiritigenin 2'-0- methyltransferase gene under salt stress - Niron, Harun. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Soil salinity has been one of the major problems in agriculture for many years. Nearly 20% of all cultivated land and half of irrigated land of world soil are saline and these levels are expected to rise in the future which will result in further crop yield reduction. Phaseolus vulgaris L. (common bean) is a legume crop with great value in the world with its nutritional and agricultural features, yet it is fairly susceptible to salt stress. Thus to understand the underlying mechanism of salt stress tolerance in plants become a necessity to eventually develop salt tolerant varieties. Our previous studies on transcriptome analysis of common bean under salt stress has revealed a major differential expression in transcripts of secondary metabolism which undoubtedly plays role in both biotic and abiotic stress responses. Further bioinformatics analysis on the transcriptome data has pointed out many salt responsive genes. A secondary metabolism gene, Isoliquiritigenin 2’-O-methyltransferase (ChOMT) has emerged as a prominent gene in salt-tolerance responses from the in silico analysis of salt induced transcripts in a salt-tolerant common bean variety. Overexpression of common bean ChOMT gene in Arabidopsis thaliana model enhanced salt tolerance of transgenic plants possibly by creating an impact on (i) accumulation of organic solute content and architectural change in root tissues to compensate adverse effect of osmotic stress and increase in the chance to absorb and conduct water to ensure biomass, and (ii) protection of seed integrity via increase in the viability and vigor of seeds. Our results suggest that ChOMT can be a good candidate gene to improve crops for salt stress tolerance.
Keywords: Soils, Salts in.